THE USING FRESTO APPLICATION TO TEACHING WRITING SKILLS OF NARRATIVE TEXT - Mudrikah (CV. Mitkom Indotama, 2024)
Writing skills are very important skills for students and will always be used by students in learning activities at school and outside of school if they have graduated and are involved in various activities in the community. The success of the teaching and learning process is largely determined by the student's ability to write. Therefore, students' writing skills should be improved as early as possible in their school life. There are some texts in writing. One of them is the narative text. A narrative text is a non-fiction story that can be a fairy tale, myth, folklore, animal story, and so on. The purpose of a narrative text is to entertain the reader with a story made in such a way that it is interesting. Narrative texts have three elements that must be present in a story or writing, such as orientation, complications, and resolution. E-Learning Fresto is a paid e-Learning that provides a variety of services that are useful in supporting the learning process, evaluation, and assessment of learning. Fresto also provides video call facilities that allow teachers and students to meet face-to-face and online in learning. E-Learning Fresto is an application that can help the learning process in the classroom and have a positive impact on teachers and students, make students not feel bored and make the learning process more interesting. The purpose of this study is to determine the achievement of students' writing skills in writing narrative texts with and without the application of fresto. The population is 36 students of class X TEI 2 SMK N 4 Semarang. The author took one class as an experimental class. Research instruments in the form of tests, there are two types of tests, namely pre-test and post-test. Written tests are used to collect data. After data collection, there was a significant difference between before and after learning using the fresto application. The results of the study were that the average score of students who wrote narative texts without fresto application was 77.41667 and the average score of students after using the fresto application in writing narative texts was 89.86111 KEY WORDS: Writing, Narative Text, Fresto App